Evidence of Illegitimate Recombination Between Two Pasteurellaceae Plasmids Resulting in a Novel Multi-Resistance Replicon, pM3362MDR, in Actinobacillus pleuropneumoniae - Yinghui Li; Yinghui Li; Giarlã Cunha da Silva; Yanwen Li; Ciro C. Rossi; Roberto Fernandez Crespo; Susanna M. Williamson; Paul R. Langford; Denise Mara Soares Bazzolli; Janine T. Bossé (Frontiers in Microbiology, 2018)
Evidence of plasmids carrying the tetracycline resistance gene, tet(B), was found in the previously reported whole genome sequences of 14 United Kingdom, and 4 Brazilian, isolates of Actinobacillus pleuropneumoniae. Isolation and sequencing of selected plasmids, combined with comparative sequence analysis, indicated that the four Brazilian isolates all harbor plasmids that are nearly identical to pB1001, a plasmid previously found in Pasteurella multocida isolates from Spain. Of the United Kingdom isolates, 13/14 harbor plasmids that are (almost) identical to pTetHS016 from Haemophilus parasuis. The remaining United Kingdom isolate, MIDG3362, harbors a 12666 bp plasmid that shares extensive regions of similarity with pOV from P. multocida (which carries blaROB-1, sul2, and strAB genes), as well as with pTetHS016. The newly identified multi-resistance plasmid, pM3362MDR, appears to have arisen through illegitimate recombination of pTetHS016 into the stop codon of the truncated strB gene in a pOV-like plasmid. All of the tet(B)-carrying plasmids studied were capable of replicating in Escherichia coli, and predicted origins of replication were identified. A putative origin of transfer (oriT) sequence with similar secondary structure and a nic-site almost identical to that of RP4 was also identified in these plasmids, however, attempts to mobilize them from an RP4-encoding E. coli donor strain were not successful, indicating that specific conjugation machinery may be required.